2016
DOI: 10.1007/s10792-016-0228-1
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser cyclophotocoagulation in Indian eyes: efficacy and safety

Abstract: Diode laser cyclophotocoagulation (DLCP) has emerged as a time-tested procedure for end-stage glaucoma with fewer complications. By means of this study, we have evaluated its wide indications, its efficacy, and safety in darkly pigmented Asian Indian eyes. Ninety-one eyes with uncontrolled glaucoma presenting to glaucoma clinic of a tertiary care center over a period of 6 years were scheduled for DLCP. The semiconductor diode laser with a G probe was used with laser energy delivered about 1.5 mm behind the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Certain studies reveal a correlation between total amount of energy and success rate 6,16 while others fail to detect this association. 7,9,11 In our study, no association was found between energy delivered and postoperative IOP. This discrepancy may stem from the fact that there is really no anatomic landmark during TS-CPC to ensure exact placement of the probe tip over the ciliary body and no method available to assess the energy delivered to the ciliary body tissue.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Certain studies reveal a correlation between total amount of energy and success rate 6,16 while others fail to detect this association. 7,9,11 In our study, no association was found between energy delivered and postoperative IOP. This discrepancy may stem from the fact that there is really no anatomic landmark during TS-CPC to ensure exact placement of the probe tip over the ciliary body and no method available to assess the energy delivered to the ciliary body tissue.…”
Section: Discussioncontrasting
confidence: 67%
“…In a study by Murphy et al 2 in which TS-CPC was applied over 270° of the ciliary body, the IOP reduction rate was found to be 52.6% in the first 7 months of follow-up. In a similar study, Singh et al 11 found the reduction in IOP to be 58.5% at 9 months post-treatment. In the current study, the IOP reduction rate was 30.9% and 39.0% at 3 and 22.2 months, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Our rate of Cumulative success (%) ± SE (95% confidence interval) 3 months 100.0 ± 100.0 (100.0, 100.0) 100.0 ± 100.0 (100.0, 100.0) N 34 34 6 months 91.1 ± 4.9 (81.9, 100.0) 88.1 ± 5.6 (77.9, 99. [20][21][22]. In our study, 7.9% of patients developed hyphema in the early postoperative follow-up period that spontaneously resolved in all but one patient with a concurrent diagnosis of malignant iris melanoma.…”
Section: Discussionsupporting
confidence: 44%
“…The success rate was 77.2% after the first week, 68.1% after the first month, 72.2% at 3 months, and 54.5% at 12 months, results that are similar to those of other studies. Singh et al ( 21 ) reported a success rate of 70% and Grueb et al ( 16 ), a 36.7% success rate, with different periods of follow-up.…”
Section: Discussionmentioning
confidence: 99%